Moral Aspects in the Main Character of Strange Case of Dr Jekyll and Mr. Hyde - Sugianti Somba (Journal of English Language and Culture, 2018)
Strange Case of Dr Jekyll and Mr. Hyde’s novel that is full range of emotion, incident, mystery and horror aspects, which makes the reader’s feeling unsteady. This novel tells us about a dual personality much depicted in plays and films, also influential in the growth of understanding of the subconscious mind through its treatment of a kind and intelligent physician who turns into a psychotic monster after imbibing a drug intended to separate good from evil in a personality. The purpose of this study is to describe the moral aspects in the main character in Strange of Dr. Jekyll and Mr Hyde. In this research method, the writer used two sources of data, the main source and the secondary source. The main source is taken from novel entitled Strange Case of Dr Jekyll and Mr. Hyde and the secondary source is taken from Internet, and furthermore. The result of this research showed that moral aspects of Mr. Utterson; as an individual is a good person; he had good relation to society and he had a good relation to God. So he is a kind person.Keywords: moral aspects, main character